Contribuições ao processo computacional para análise de pedidos de indenização por danos em equipamentos elétricos - Mendonça, Marcus Vinícius Borges (2010)
The increasing number of refunding requests related to electrical and electronic equipment damages has attracted the attention of the electric utilities, consumers, regulatory and other government agencies. Such concerns are not associated only with the financial contents involved, but especially with the social impacts associated to requests, decisions, conflicts and other issues involving the relationship between utilities and their consumers. Therefore, this theme has been encouraging investigations towards the improving of the refunding analysis, diffusion of knowledge of the correlation between the disturbances and final equipment effects. In the same direction goes efforts at providing guidelines to offer products with greater level of withstand capability facing typical disturbances in electric system. Whilst the first highlighted topic is concentrated in the establishment of a fair and cohesive evaluation process of repayment, the second aims at obtaining data to clarify the relationship between efforts and electrical impacts upon the equipments, finally, the third mentioned area covers aspects related to improvements in the fabrication of various devices frequently found in residential, commercial and industrial installations. This scenario brings out the developments that motivate this thesis, which is aimed at producing and enhance methods to improve researches previously conducted to the achievement of a systematic mechanism and computational way of emitting technical based reports regarding the refunding request consistence. The main subjects focused in this work are directed to the new guidelines of the Brazilian rules concerning equipment connection to the network, improvements in some equipment models, computational implementation of grounding systems modeling in the study and validation of the overall process through real cases.